مساهمة صغار مقاولي البناء في تجسيد مشروع البناء الذاتي دراسة ميدانية مخصص التجزئة بمنطقة واد نشو بلدية غرداية (مجلة الواحات للبحوث والدراسات, 2022)
ملخصتهدف هذه الدراسة إلى ابراز أهمية وواقع اسهامات صغار المقاولين في تجسيد مشروع الدولة الخاص بالقضاء على ازمة السكن في اطار البناء الريفي، وهو مشروع تنمية محلية مهم على مستوى الجبهة الاجتماعية، أين تم جمع بيانات هذه بإجراء مقابلة مع صغار المقاولين الذين ورشهم في حالة نشاط بمنطقة واد نشو خلال شهر جانفي ، ومن أجل الإجابة على هذه الإشكالية قمنا بالاستعانة برنامج التحليل النوعي (Nvivo) في تنظيم وإدارة وتحليل البيانات، حيث بينت نتائج الدراسة أن مشاركة صغار المقاولين في مشروع قطعة أرض واعانة مالية هي تسهيل لصب الاعانات المالية أكثر من تشييد مساكن كاملة في اطار تسيير الجماعات المحلية لازمة السكن، وأوصت الدراسة بأنه لابد من النظر للمشروع على أنه أزمة يجب حلها لا ملف يتم تسييره. كلمات دالة : المستفيدين ، صغار المقاولين ،اعانة مالية ، بنية تحتية ، بناء   Abstract This study aims to identify the reality of the contributions of small contractors in projects of residential, in order to eliminate the housing crisis through rural construction, it is a socially important local development project, and we collected the data of this study using an interview with small contractors whose workshops are active in the Wadi nsho area. in order to answer this problem we have used Nvivo qualitative analysis software in organizing and analyzing the data.The study reached the following results:• ·         The participation of small contractors in the project of a plot of land and financial subsidies is to facilitate the casting of subsidies, and not for the construction of full housing;• ·         Therefore, the study recommended that the project should be considered as a crisis that must be solved and not a file to be managed.Key words: beneficiaries; small contractors; financial subsidies; infrastructure; construction.